STEREOTYPES, PREJUDICE AND DISCRIMINATION IN TONY MORRISON'S THE BLUEST EYE (1970): SOCIAL PSYCHOLOGICAL APPROACH - WAHYUDI, ANIS TRI (2011)
The objective of the study is to analyze the novel based on its structural analysis and based on social psychological analysis. This study is a qualitative study. The object of the study is Tony Morrison's The Bluest Eye published in 1970 in New York by Rosetta Books LLC. The data sources are divided into two, namely primary data source and secondary data source. The primary is the novel itself and the secondary data source is other sources related to the analysis such as the author biography, books of literary theory and also psychology books, particularly related to social psychological books. The method of data collection is library research. The technique of data analysis is descriptive analysis. The results of the study are as follows. First, Tony Morrison's The Bluest Eye was portrayed Beauty is social construction which is determined by the dominant culture that was illustrated on the characters, characterization, narration or dialog. Second, Tony Morrison succeeded to show the reality of human life through her novel, especially social relations that appear in society between the black and white race including of stereotypes, prejudice and discrimination that influence on social psychology of person.